2021
DOI: 10.2147/rru.s312128
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Androgen Deprivation Therapy Effects on Perioperative Outcomes Prior to Radical Prostatectomy: Eleven Years of Experiences at Ramathibodi Hospital

Abstract: Objective The aim of this study was to demonstrate the efficacy of neoadjuvant androgen deprivation therapy (NADT) on perioperative outcomes in patients who underwent radical prostatectomy (RP). Materials and Methods From January 2008 to July 2018, we collected retrospective data of patients with clinically localized prostate cancer who underwent RP to assess their perioperative and pathological outcomes. The data included age, body mass index (BMI), serum prostate spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…However, the clinical findings of neoadjuvant hormone therapy (NHT) before radical prostatectomy are inconsistent among various studies. Some studies have found that neoadjuvant hormone therapy prior to RP helps reduce the incidence of positive surgical margins and lymph node infiltration [ 7 , 8 ], but others have suggested that neoadjuvant hormone therapy prior to RP does not have a significant survival benefit for patients, including overall survival and disease-free survival [ 9 ], and therefore preoperative neoadjuvant therapy is not specifically recommended by current guidelines for patients with high-risk prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical findings of neoadjuvant hormone therapy (NHT) before radical prostatectomy are inconsistent among various studies. Some studies have found that neoadjuvant hormone therapy prior to RP helps reduce the incidence of positive surgical margins and lymph node infiltration [ 7 , 8 ], but others have suggested that neoadjuvant hormone therapy prior to RP does not have a significant survival benefit for patients, including overall survival and disease-free survival [ 9 ], and therefore preoperative neoadjuvant therapy is not specifically recommended by current guidelines for patients with high-risk prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We performed ORP in a retropubic fashion through a low midline incision (Fig. 1 A) according to our regular ORP approach [ 10 ]. Briefly, the space of Retzius was developed using blunt and sharp dissection along the outside of the left umbilical ligament.…”
Section: Methodsmentioning
confidence: 99%
“…The LRP was performed in an extraperitoneal fashion using 5 trocars with some modification from the standard port positions [ 10 ] to facilitate graft injury prevention (Fig. 1 B, C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation